Management of temporomandibular joint ankylosis in Yemeni children by metatarsal bone grafts - Al Hudaid, Ali; Aldialami, Abdullwahab (Journal of Oral Research, 2019)
This study aimed to evaluate temporomandibular joint reconstruction in Yemeni children with metatarsal bone graft after release of ankylosis. Methodology: Ten patients ?12 years of age, comprising eight unilateral and two bilaterally TMJ ankylosis, were selected for this study. These patients underwent reconstruction with 10 non-vascularized metatarsal grafts. The reconstructed joints were then followed for an average of 1 year. Measures of opening, symmetry, and clinical symptoms relating to the reconstructed joints were assessed. Results: Mean pre-operative interincisal aperture was 8.2mm, and immediate post-operative aperture 23.4mm. At the end of the follow-up period, acceptable results were achieved in 8 out of 10 cases, with adequate mouth opening of 35.6mm in 8 out of 10 patients and overall interincisal aperture of 30.3mm. Re-ankylosis occurred in two bilaterallytreated patients at the end of follow-up. Subjectively, 80% of the patients rated their function as satisfactory and were able to occlude and masticate without any difficulty.